Decomposition of wheat straw and stabilization of microbial products - Voroney, R. P., author; Anderson, D. W., author; Paul, E. A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1989)
This research examined the effects of soil environment on the decomposition of cereal crop residues and stabilization of microbial products in the field. Microplots at semi-arid and subhumid field sites were amended with 14C-, 15N-labelled wheat straw and with 14C-labelled glucose plus 15N-labelled NH4NO3 and the fate of the residual C and N was monitored over 10 yr. Mineralization of C and N derived from wheat straw was greater at the site in the more moist environment in the short term (2 yr). In the long term (up to 10 yr), however, the residual C and N at this site decayed at a slightly slower rate, providing evidence of stabilization of organic material in chemically resistant forms, as compared to possible physical protection in the semi-arid clay-textured soil. The total recovery of labelled N was 22.5–24% in the harvested crops with 13.4–16% remaining in the surface soil by the end of the study. Mineralized labelled organic N was used with an efficiency ranging from 32 to 51%. However, after summer fallow the crop apparently used mineralized labelled N with an efficiency of only 7%. This study showed that moistness of the soil environment has a considerable effect on residue decomposition. Stabilization of humic material derived from residues relates more to the recalcitrance of microbial products and their interactions with soil mineral colloids than to the nature of the original residue.
Keywords: physical protection; chemical recalcitrance; mineralization rates; microbial turnover; crop residues; plant N use-efficiency